2011
DOI: 10.1051/0004-6361/201015367
|View full text |Cite
|
Sign up to set email alerts
|

Structure of evolved cluster-forming regions

Abstract: Context. An approach towards understanding the formation of massive stars and star clusters is to study the structure of their hot core phase, an evolutionary stage where dust has been heated, but molecules have not yet been destroyed by ultraviolet radiation. These hot molecular cores are very line-rich, but the interpretation of line surveys is also hampered by poor knowledge of the physical and chemical structure. Aims. To constrain the radial structure of high-mass star-forming regions containing hot cores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 38 publications
(75 citation statements)
references
References 70 publications
4
71
0
Order By: Relevance
“…The data points can be roughly fitted by a function f (x) = a · x b + c with an exponent of b = −1.3±0.5 and a constant c = (35±11) K for θ > 6 in the outer parts or envelope where the temperature gradient becomes flat. This is consistent with models of hot cores which predict a steep increase inwards (Rolffs et al 2011). The profile could be affected by the fit function, where in the optical thick limit, T and θ are inversely proportional to each other with T ∝ 1/θ, but this only concerns few molecules.…”
Section: General Remarkssupporting
confidence: 88%
“…The data points can be roughly fitted by a function f (x) = a · x b + c with an exponent of b = −1.3±0.5 and a constant c = (35±11) K for θ > 6 in the outer parts or envelope where the temperature gradient becomes flat. This is consistent with models of hot cores which predict a steep increase inwards (Rolffs et al 2011). The profile could be affected by the fit function, where in the optical thick limit, T and θ are inversely proportional to each other with T ∝ 1/θ, but this only concerns few molecules.…”
Section: General Remarkssupporting
confidence: 88%
“…Nevertheless, clear global infall at clump scale is difficult to detect (López-Sepulcre et al 2010;Reiter et al 2011) since local star formation also creates infall and outflow signatures. Infall rates of star-forming clumps are observed to be small, about 10% of the free-fall velocity (Rolffs et al 2011;Tan et al 2014;Wyrowski et al 2016), supporting a quasi-static picture. Rygl et al (2013) suggested that the infall and outflow only become evident when the clump-cloud column density contrast exceeds 2 and, at more evolved stage, the infall is halted.…”
Section: Introductionmentioning
confidence: 71%
“…We use the tabulated dust opacity from Ossenkopf & Henning (1994) for dust without grain mantles and no coagulation, as found to best fit the Sagittarius B2 region by Rolffs et al (2011b). Including the free-free emission we cover the frequency range from 40 GHz up to 4 THz.…”
Section: Images and Post-processingmentioning
confidence: 99%